2004
DOI: 10.1111/j.1365-2044.2004.03740.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reliability between a nurse and anaesthetist of tests used for predicting difficult tracheal intubation

Abstract: SummaryWe examined the interobserver reliability, between a nurse and anaesthetist, of five tests used to predict difficult tracheal intubation: mouth opening; thyromental distance; head and neck movement; mandibular luxation; and assessment of oropharyngeal view. For each test, an anaesthetic nurse and a specialist registrar anaesthetist were trained to use a standard method of examination. Most of the tests had either good or very good reliability. Assessment of mouth opening demonstrated only moderate relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…However, they had only a short previous practice in anesthesia and airway management in the operating room. Although previous studies have shown generally variable agreement and inconsistency between assessors irrespective of their qualification (two specialists 8 , two residents 8,11 , specialist vs. resident 22 , anesthetist vs. nurse 10 ), the assessor's level of expertise may also influence the accuracy 8 . The only goal of the study was to compare the agreement of paired measurements of two assessors and not to determine the ability of the tests to predict DI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, they had only a short previous practice in anesthesia and airway management in the operating room. Although previous studies have shown generally variable agreement and inconsistency between assessors irrespective of their qualification (two specialists 8 , two residents 8,11 , specialist vs. resident 22 , anesthetist vs. nurse 10 ), the assessor's level of expertise may also influence the accuracy 8 . The only goal of the study was to compare the agreement of paired measurements of two assessors and not to determine the ability of the tests to predict DI.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, data describing its reproducibility are contradictory. Hilditch et al 10 found excellent agreement between a nurse and anesthesiologist in the measurement of TMD (ICC=0.85). We found poor to fair agreement depending on the coefficient used (ICC= -0.002, Pearson's correlation coefficient = 0.265).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[145] The reported incidence of a difficult laryngoscopy and tracheal intubation varies from 1.5% to 13% in patients undergoing elective surgery. [6] Because of potentially serious consequences of failed tracheal intubation, considerable attention has been focused on attempts to predict patients in whom laryngoscopy and intubation might be difficult,[57] and in this regard combination of different test and scores are developed, but none of them have proven to be totally reliable. [589]…”
Section: Introductionmentioning
confidence: 99%
“…Using airway assessment tests and clinical criteria, difficulty with airway management may be anticipated (3). However, patient factors, observer variability and experience contribute to poor reliability estimates in some bed-side tests (4). Consequently, unanticipated difficult tracheal intubation continues to occur with a low but consistent incidence.…”
Section: Introductionmentioning
confidence: 99%